2006
DOI: 10.1097/01.mpg.0000228110.83616.92
|View full text |Cite
|
Sign up to set email alerts
|

Alanine Amino Transferase Concentrations Are Linked to Folate Intakes and Methylenetetrahydrofolate Reductase Polymorphism in Obese Adolescent Girls

Abstract: Our data suggest that folate intake and the MTHFR polymorphism represent a part of the link between antioxidant status and liver disease in obese adolescent girls.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0

Year Published

2008
2008
2018
2018

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 49 publications
2
18
0
Order By: Relevance
“…We did not observe any significant change in aminotransferases activities in neither tissue tested, despite the relevant oxidative and histological alterations found in our study. Conversely, Frelut et al (2006) recently showed a positive correlation between ALT activity and Hcy plasma levels in obese adolescent girls. Experimental models of hyperhomocysteinemia in rats provide evidence for increased serum ALT and AST activities, associated with ROS production and hepatic lipid peroxidation (Huang et al, 2001; Woo et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
See 1 more Smart Citation
“…We did not observe any significant change in aminotransferases activities in neither tissue tested, despite the relevant oxidative and histological alterations found in our study. Conversely, Frelut et al (2006) recently showed a positive correlation between ALT activity and Hcy plasma levels in obese adolescent girls. Experimental models of hyperhomocysteinemia in rats provide evidence for increased serum ALT and AST activities, associated with ROS production and hepatic lipid peroxidation (Huang et al, 2001; Woo et al, 2006).…”
Section: Discussionmentioning
confidence: 95%
“…Liver injury could be identified by serum markers, such as alanine aminotransferase (ALT) and aspartate aminotransferase (AST), which are increased as a result of hepatic necrosis (Ozer et al, 2008). Hcy has been related to hepatotoxic conditions in numerous reports, which have showed a positive correlation between hyperhomocysteinemia and plasma aminotransferases activities in clinical and experimental studies (Huang et al, 2001; Woo et al, 2006; Frelut et al, 2006). In this context, an increase of ALT and AST activities was observed in serum of hyperhomocisteinemic rats (Woo et al, 2006) and of ALT in plasma hyperhomocysteinemic patients (Frelut et al, 2006).…”
Section: Introductionmentioning
confidence: 99%
“…Previous researches could also elicit positive association of obesity and hypertension, coronary artery disease or liver diseases with MTH-FR C677T mutations [32][33][34]. Also Thwnashom et al have reported that folic acid and MTHFR gene polymorphism were found to be significantly related to the overweight/obese and control groups in logistic regression analysis [35].…”
Section: Discussionmentioning
confidence: 99%
“…Furthermore, in anti-hepatitis C virus antibody seropositive individuals, Wang et al found that smoking and higher alcohol consumption independently elevated serum ALT level (38). Moreover, liver damage in obese adolescent girls was enhanced by low folate status and the MTHFR C677T mutation (39).…”
Section: Discussionmentioning
confidence: 99%